Developing a Pop-Up Book to Enhance Indonesian Narrative Text Comprehension for Fourth-Grade Elementary School Students - Aida, Nun Asmi; Rahman, Alvin Yanuar; Saefuddin, Asis; Widowati, Kawuryansih (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2025)
This study presents a comprehensive development of an interactive Pop-Up Book designed as an educational tool for Indonesian narrative texts, specifically tailored for fourth-grade students at the Islamic Elementary School of Bahrul Ihsan in Bandung City. Employing a rigorous Research and Development (R&D) methodology, the study utilized the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to ensure a systematic and empirical approach. Data was gathered through a variety of methods, including interviews with classroom teachers, validation questionnaires from media and material experts, and direct feedback from both the fourth-grade teacher and students following the media's implementation. The results indicate that the learning medium possesses high validity and practicality. Validation from experts was highly positive, with media experts assigning a remarkable rating of 99% and material experts rating it at 93%, both categorized as